2013
DOI: 10.1017/s1368980013002334
|View full text |Cite
|
Sign up to set email alerts
|

Inverse relationship between vitamin D status and insulin resistance and the risk of impaired fasting glucose in Korean children and adolescents: the Korean National Health and Nutrition Examination Survey (KNHANES) 2009–2010

Abstract: Objective: To investigate whether low vitamin D status was related to insulin resistance (IR) or impaired fasting glucose (IFG) in Korean adolescents, after adjusting for total body fat mass (FM). Design: A cross-sectional study. Results: Age-, sex-, season-and physical-activity-adjusted regression models showed that serum 25(OH)D levels were significantly related to markers of adiposity (P 5 0?016 for FM (g), P 5 0?023 for FM (%) and P 5 0?035 for fat mass index). When the participants were stratified into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 31 publications
(70 reference statements)
2
37
1
2
Order By: Relevance
“…Previous clinical studies have shown an inverse association between low vitamin D status and insulin resistance that was independent of total adiposity (BMI and total fat mass) (31)(32)(33)(34)(35). However, this study shows that the inverse relation between vitamin D and insulin resistance is indeed confounded by adiposity, particularly central adiposity.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Previous clinical studies have shown an inverse association between low vitamin D status and insulin resistance that was independent of total adiposity (BMI and total fat mass) (31)(32)(33)(34)(35). However, this study shows that the inverse relation between vitamin D and insulin resistance is indeed confounded by adiposity, particularly central adiposity.…”
Section: Discussioncontrasting
confidence: 56%
“…When controlling for BMI or total fat mass, the association between vitamin D status and insulin resistance continued to persist in some studies (31)(32)(33)(34)(35) but was lost in others (36,37). However, BMI is a measurement of body mass relative to height and does not directly assess total adiposity or its anatomical distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Another paper about patients with prediabetes (i. e., impaired fasting glucose or impaired glucose tolerance) reported that individ-uals with the lowest D vitamin concentrations had the highest degree of insulin resistance (using HOMA index) [3]. Similar associations were found also in children and adolescents [32]. In exploratory analysis, after exclusion all subjects with impaired fasting glucose or metabolic syndrome (i. e., those with potentially pre-diabetic state) we confirmed the independent association between D vitamin status and insulin sensitivity.…”
Section: Vitamin D and Impaired Glucose Metabolismmentioning
confidence: 76%
“…Quality evaluation of the articles included showed that the highest score was 18 points and two articles scored this value 39,40 . One article scored 17 points 41 and two articles were quantified with 16 points 42,43 .…”
Section: Methodological Qualitymentioning
confidence: 99%